Bacteriological study and antibiotic sensitivity profile in patients with ear discharge visiting ENT OPD at tertiary care center - Patel, Kailas R.; Fefar, Alpesh D.; Khavdu, Paresh J.; Mistry, Sejal N.; Mehta, Manish R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Otitis media (OM) is a big menace in countries like India. Chronic suppurative otitis media (CSOM) is chronic inflammation of middle ear, which affects the tympanic membrane, middle ear mucosa and other middle ear structures characterised by the presence of persistent perforation or persistent mucoid or muco-purulent discharge for at least 8 weeks. Variety of organisms founds in patients suffering from chronic otitis media like, Pseudomonas, Staphylococcus aureus, Proteus mirabilis, Klebsiella pneumonia and Escherichia coli found. The pattern of organisms varies in different geographical areas. The objectives of the study were to isolate bacteria from patients with ear discharge, to find out antibiotic sensitivity of isolated organisms Methods: This is an observational cross sectional study done in the OPD department of otorhinolaryngology, at P.D.U medical college and hospital, Rajkot, for a period of six months from January 2017 to June 2017. A total number 200 patients of both gender between 5 to 74 years who visited the OPD department of otorhinolaryngology with chronic ear discharge taken for study. Results: Out of 200 patients of 5-74 years with chronic suppurative otitis media were examined and out of this Hundred and twelve (54%) of the patients were males with mean age of 33.44. Pseudomonas aeruginosa was the commonest identified organisms the sensitivity pattern highly favoured Pipercillin, Amikacin and Polymyxin B, Cefoparazone. Conclusions: Chronic otitis media is more prevalent in males than females. Commonest organisms found were Pseudomonas aeruginosa followed by Staphylococcus aureus. Piperacillin, Amikacin, Gentamicin, Polymyxin B and Cefoperazone were found most effective agents against Pseudomonas aeruginosa.